Secure medical image transmission for healthcare applications using cooperative relaying based on physical layer security - Ali Kuhestani; Mohammad Ali Sebtonabi; Roozbeh Rajabi; Mohammadreza Keshavarzi (مدیریت مهندسی و رایانش نرم)
In this article, a new idea and method to protect image against illegal users has been proposed. Considering that in medical images, most of the experts' emphasis is on the part of the image that shows the disease, in this article, the image is first divided into two parts namely, main and background parts, and then the transmitter estimats regarding the capacity of legal and non-legal channels. Here, the transmitter decides whether to send the main part or the background part, i.e., when the capacity of the legal channel is greater than the capacity of the eavesdropping channel, the main part of the image is sent, and when the capacity of the eavesdropping channel is greater than the legal channel, the background part is sent. In addition, in this article, due to the large distance between the transmitter and the receiver and the effect of the path loss, a relay is adopted to boost the signal. Simulation results are provided to highlight the effectiveness of our proposed cooperative relaying idea.